An in vitro evaluation of the effect of hydroxycinnamic acids on the growth and hydrolytic enzyme production in Fusarium oxysporum f. sp. albedinis. (8th November 2021) - El Hassni, Majida; Laadouzaa, Hamza; El Hadrami, Abdelbasset; Dihazi, Abdelhi; Rakibi, Youness; Lemjiber, Naima; Naamani, Khalid
Abstract: Activation of the phenylpropanoids pathway in date palm ( Phoenix dactylifera L.) roots is a key defense mechanism against Fusarium oxysporum f. sp. albedinis (Foa), the causal agent of bayoud. In this study, the effects of four hydroxycinnamic acids (0-5 µm/ml), mainly caffeic acid, p -coumaric acid, ferulic acid and sinapic acid, on fungal biomass production, sporulation and hydrolytic enzymes (protease, cellulase, polygalacturonase and pectinemethyl-esterase) of Foa were investigated. In vitro tests results showed an overall inhibition effect of caffeic and p- coumaric acids compared to ferulic and sinapic acids. Caffeic and p -coumaric acids at 5 µmol/ml had highest inhibition rates of mycelial growth and sporulation ranging from 73 to 80% and 97 to 100%, respectively. For hydrolytic enzyme activities, the inhibition rate of hydoxycinnamic acids tested for protease ranged from 80 to 100%, 63 to 98% for cellulase, 91 to 100% for pectinemethyl-esterase and 59 to 99% for polygalacturonase. Nevertheless, it was found that sinapic acid, at low concentration (0.5 µmol/ml), has no inhibition effect on mycelial growth and hydrolytic enzyme activities. Additionally, the half maximal inhibitory concentration (IC50 ) has also been determined to compare the different acids effects.